2004
DOI: 10.1039/b401052c
|View full text |Cite
|
Sign up to set email alerts
|

New sterically hindered Hf, Zr and Y β-diketonates as MOCVD precursors for oxide films

Abstract: New Zr, Hf and Y 2,7,7-trimethyl-3,5-octanedionates (tod) as well as the corresponding Cu b-diketonate have been synthesized and characterized by FT-IR, elemental analyses, TGA, and 1 H NMR or ESR. The molecular structure of Hf(tod) 4 has been determined by single-crystal X-ray diffraction, the metal displays a square antiprismatic geometry. Zr, Hf and Y b-diketonates were investigated as precursors for MOCVD deposition of ZrO 2 , HfO 2 and yttria-stabilized hafnia thin films. The films were characterized by X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…The bombarding ions remove the loosely bonded atoms and thus also help in reducing the degree of contamination in the deposited films. The advantages of octanedionate precursors used in this deposition are that they are volatile as compared to heptanedionate precursors and result in less carbon contamination in the deposited films as reported by Pasko et al [18] and evident from the observed transparency of yttria doped films in our case. Carbon co-deposition using heptanedionate precursors have been earlier reported.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…The bombarding ions remove the loosely bonded atoms and thus also help in reducing the degree of contamination in the deposited films. The advantages of octanedionate precursors used in this deposition are that they are volatile as compared to heptanedionate precursors and result in less carbon contamination in the deposited films as reported by Pasko et al [18] and evident from the observed transparency of yttria doped films in our case. Carbon co-deposition using heptanedionate precursors have been earlier reported.…”
Section: Resultssupporting
confidence: 67%
“…Hydrogen in case of heptanedionate precursors is replaced by methyl radical in octanedionate precursor, leading to enhanced volatility due to the shielding effect of methyl radical [14]. Pasko et al have made a comparative study on properties of monoclinic ZrO 2 films deposited using Zr(tod) 4 and Zr(thd) 4 precursors and reported that octanedionate precursors are able to produce higher growth rate at lower temperature compared to the heptanedionate precursors [18]. As reported in the literature approximately 3-5 mol% of yttria is required for formation of PSZ while 8 mol% yttria stabilizes zirconia in cubic phase (YSZ) [2,3].…”
Section: Resultsmentioning
confidence: 96%
“…Thus, precursors with lower decomposition temperatures are desirable. Recently the b-diketonates Hf(tod) 4 (tod: 2,7,7-trimethyl-3,5-octanedionate) [5] and Hf(tmnd) 4 (tmnd: 2,2,8,8-tetramethyl-4,6-nonanedionate) [6] have been proposed, and tested for the deposition of HfO 2 . They allow higher growth rates at a lower deposition temperature than Hf(tmhd) 4 ; however no electrical results have been shown yet.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, [HfCl 4 ] is a lowvolatility solid which needs substrate temperatures of at least 800°C for oxide deposition, [7] making it unsuitable for many IC applications where a low thermal budget is required. The b-diketonates, [Hf(thd) 4 ] (thd = 2,2,6,6,-tetramethyl-3,5-heptanedionate), [8] [Hf(tod) 4 ] (tod = 2,7,7-trimethyl-3,5-octanedionate), [8] and [Hf(tmnd) 4 ] [9] have been investigated, but they also require relatively high growth temperatures, and oxide films deposited from b-diketonates are often contaminated with carbon. Although the nitrate complex [Hf(NO 3 ) 4 ] has been used for the MOCVD of high-purity HfO 2 films, [10,11] concerns about the stability of anhydrous metal nitrates may restrict its application.…”
Section: Introductionmentioning
confidence: 99%